2019
DOI: 10.1177/0023830918823230
|View full text |Cite
|
Sign up to set email alerts
|

Is All Formulaic Language Created Equal? Unpacking the Processing Advantage for Different Types of Formulaic Sequences

Abstract: Research into recurrent, highly conventionalized “formulaic” sequences has shown a processing advantage compared to “novel” (non-formulaic) language. Studies of individual types of formulaic sequence often acknowledge the contribution of specific factors, but little work exists to compare the processing of different types of phrases with fundamentally different properties. We use eye-tracking to compare the processing of three types of formulaic phrases—idioms, binomials, and collocations—and consider whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 108 publications
10
114
1
1
Order By: Relevance
“…In line with previous literature (e.g., Carrol & Conklin, 2014, 2015, 2019; Carrol, Conklin, & Gyllstad, 2016; Conklin & Pellicer-Sánchez, 2016; Underwood, Schmitt, & Galpin, 2004; Vilkaitė, 2016; Vilkaitė & Schmitt, 2017), two interest areas were selected for data analysis: the phrase-final word (e.g., 会议 “ meeting ”) and the whole phrase (e.g., 参加会议 “ attend the meeting ”). It was important to include the final word as an interest area, as well as the whole phrase, because the final word in MWEs “may be predictable and therefore elicit shorter fixations and more skipping” (Conklin, Pellicer-Sánchez, & Carrol, 2018, p. 102).…”
Section: Data Analysis and Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous literature (e.g., Carrol & Conklin, 2014, 2015, 2019; Carrol, Conklin, & Gyllstad, 2016; Conklin & Pellicer-Sánchez, 2016; Underwood, Schmitt, & Galpin, 2004; Vilkaitė, 2016; Vilkaitė & Schmitt, 2017), two interest areas were selected for data analysis: the phrase-final word (e.g., 会议 “ meeting ”) and the whole phrase (e.g., 参加会议 “ attend the meeting ”). It was important to include the final word as an interest area, as well as the whole phrase, because the final word in MWEs “may be predictable and therefore elicit shorter fixations and more skipping” (Conklin, Pellicer-Sánchez, & Carrol, 2018, p. 102).…”
Section: Data Analysis and Resultssupporting
confidence: 92%
“…A mixed design was employed, treating phrase type as a within-group variable, age group as a between-group variable, and the eye-tracking measures as dependent variables. In line with Carrol and Conklin (2019), Sonbul (2014), and Yi et al (2017), four measures were examined: first fixation duration (early), first pass reading time (middle), dwell time, and fixation count (late, see Figure 1). The former three measures were duration measures, which reflected reading times, while the latter measure was a count measure, which provided the number of fixations.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Formulaic language has been referred to using different terms: formulae , formulaic sequences , prefabricated patterns , multiword units or sequences , to mention a few (see reviews by Arnon & Christiansen, ; Wray, ). It also covers a broad range of phenomena such as idioms, collocations, phrasal verbs, binomials, and lexical bundles (Carrol & Conklin, ). This article focuses on what usually are referred to as lexical bundles, which are sequences of words that occur frequently in language, are generally corpus derived, and may or may not constitute a complete utterance.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Familiar idioms are shown to be responded to faster than matched control phrases (Cacciari et al, 2007;Cacciari & Tabossi, 1988;Conklin & Schmitt, 2008; . This fluency and idiomatic control is mainly attributed to the users' subjective familiarity with the idiomatic strings (Carrol & Conklin, 2020;Libben & Titone, 2008;Schweigert, 1986Schweigert, , 1991 . Studies of idiom variation have shown that altering the syntax affects idioms' acceptability and comprehension to various degrees (Geeraert et al, 2018;McGlone et al, 1994; .…”
Section: Introductionmentioning
confidence: 99%